Evaluating Lumbricus rubellus Performance and Vermicompost Quality in Cow Manure–Mealworm Waste Mixtures - Tamara Putri Utami; Salundik Salundik; Asnath Maria Fuah; Verika Armansyah Mendrofa (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2025)
This study examined the effect of adding mealworm (Tenebrio molitor) frass to cow manure media on the productivity of Lumbricus rubellus and the quality of the vermicompost. A completely randomized design was employed with six treatments (T0–T5), consisting of increasing proportions of frass: T0 (100% cow manure), T1 (95:5), T2 (90:10), T3 (85:15), T4 (80:20), and T5 (75:25). The T2 treatment yielded the highest earthworm biomass gain (4.95 g), cocoon production (87.94 cocoons), and media reduction (198.83 g), all statistically significant (p<0.05). Vermicompost from each treatment was assessed through a growth trial using Ipomoea reptans (water spinach) under eight media combinations (U0–U7): U0 (100% soil), U1 (soil + NPK), and U2–U7 (soil + vermicompost from T0–T5, respectively). Among these, U7 (incorporating vermicompost from T5) demonstrated the highest nutrient content (C-organic 41.51%, N 1.99%, P₂O₅ 1.99%, K₂O 1.47%) and significantly enhanced plant growth (p < 0.05). These findings indicate that moderate frass supplementation (10%) optimizes earthworm productivity, while higher inclusion levels (25%) improve vermicompost agronomic value. Thus, moderate frass addition is recommended to optimize vermicompost production and worm performance.